Alpha-1 antitripsyn deficiency and augmentation therapy in pregnancy: two case reports - Annunziata, Anna; Fiorentino, Giuseppe; Coppola, Antonietta; Cauteruccio, Rosa; Ferrentino, Laura; Fiorentino, Luigi; Calabrese, Cecilia (Frontiers in Medicine, 2024)
Alpha-1 antitrypsin deficiency (AATD) is an inherited condition characterized by reduced plasma levels of alpha-1 antitrypsin (AAT), often leading to pulmonary diseases primarily emphysema and/or chronic obstructive pulmonary disease (COPD), but also bronchiectasis, bronchial asthma or other less common disorders. Early diagnosis enables AAT augmentation therapy, which has proven to be effective in slowing down functional decline and improving survival rates. This paper presents two cases of pregnant women with rare allelic variants of AATD who received AAT augmentation therapy, exploring the limited evidence on its safety during pregnancy and the potential role of decreased serum AAT levels in pregnancy-related complications.